2022
DOI: 10.1038/s41397-022-00286-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of an extensive workflow for comprehensive clinical pharmacogenomic profiling: lessons from a pilot study on 100 whole exome sequencing data

Abstract: This pilot study is aimed at implementing an approach for comprehensive clinical pharmacogenomics (PGx) profiling. Fifty patients with cardiovascular diseases and 50 healthy individuals underwent whole-exome sequencing. Data on 1800 PGx genes were extracted and analyzed through deep filtration separately. Theoretical drug induced phenoconversion was assessed for the patients, using sequence2script. In total, 4539 rare variants (including 115 damaging non-synonymous) were identified. Four publicly available PGx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Earlier research that compared several bioinformatics algorithms for calling alleles found that the all PGx speci c bioinformatic tools worked well together 4,6 . A study, however, found that command-line-based programs had higher accuracy than web-based PGx haplotype tools like PharmaKU 10 . This could be why there is a high level of similarity among all four different tools, which are all command-line-based algorithms, in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Earlier research that compared several bioinformatics algorithms for calling alleles found that the all PGx speci c bioinformatic tools worked well together 4,6 . A study, however, found that command-line-based programs had higher accuracy than web-based PGx haplotype tools like PharmaKU 10 . This could be why there is a high level of similarity among all four different tools, which are all command-line-based algorithms, in this study.…”
Section: Discussionmentioning
confidence: 97%
“…These discrepancies in calling genotype may be due to algorithm differences, as each tool employs unique algorithms and methodologies for aligning sequencing reads, identifying variants, and translating genotypes to star alleles 10 . In addition, reference database updates 27 , indel and SVs handling, quality thresholds and lters, and phasing and haplotype reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Whole exome sequencing (WES) has been evaluated for CYP2D6 SV/CNV detection, but there are inherent technical challenges, including difficulties with coverage and SV/CNV calling that preclude clinical implementation of WES‐based CYP2D6 determination 91–95 . In addition, CYP2D6 calling from WES data is inconsistent among star‐allele calling tools, indicating limited clinical application for WES 96 . Specialized software has been developed and successfully used for CYP2D6 calling from targeted next‐generation sequencing (NGS) captures that include baits for CYP2D6 and CYP2D7 97,98 ; however, the software requires customization to the specific capture and significant adjustment to apply to other captures.…”
Section: Methods For Characterizing Cyp2d6 Structural Variantsmentioning
confidence: 99%
“…[91][92][93][94][95] In addition, CYP2D6 calling from WES data is inconsistent among star-allele calling tools, indicating limited clinical application for WES. 96 Specialized software has been developed and successfully used for CYP2D6 calling from targeted next-generation sequencing (NGS) captures that include baits for CYP2D6 and CYP2D7 97,98 ; however, the software requires customization to the specific capture and significant adjustment to apply to other captures.…”
Section: Other Methods and Platforms For Detecting Cyp2d6 Structural ...mentioning
confidence: 99%
“…In order to select the most appropriate bioinformatic tools for variant calling, it is essential to have a comprehensive understanding of the available PGx dedicated tools and their main features. Furthermore, common bioinformatics algorithms, such as SIFT, Polyphen2, FATHMM, CAD, etc., may require pre-filtration of variants for specific markers (Tafazoli et al, 2022). However, these tools often overlook variants that result in "increased or decreased function," which are crucial for determining ultrarapid and intermediate metabolizer phenotypes.…”
mentioning
confidence: 99%